2022
DOI: 10.1590/0001-3765202220200515
|View full text |Cite
|
Sign up to set email alerts
|

Germination and in vitro development of mature zygotic embryos and protein profile of seedlings of wild and cultivated Hevea brasiliensis

Abstract: The main factors governing Hevea brasiliensis germination and seedling establishment remains unclear. We examined the effect of growth regulators Indole 3-Acetic Acid (IAA) and 6-Benzylaminopurine (BAP), and their interactions on germination and the development of mature zygotic embryos (MZE) and protein profi le of Hevea brasiliensis seedlings from wild and cultivated (clone PB 250) genotypes. Embryonic axes excised from seeds (wild and clone PB 250) were inoculated in Murashige and Skoog medium (control) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Recent studies have reported that plants growing in media containing high concentrations of sucrose display higher gains in dry weight and leaf development [42]. Various studies have supported the beneficial effects of these hormones in inducing a callus in Hevea and other plant species [43][44][45][46]. The optimal regeneration potential was obtained in MH media supplemented with 1 mg/L 6-BA, 3 mg/L KT, 0.06 mg/L 2, 4-D, and 0.5 mg/L GA3.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that plants growing in media containing high concentrations of sucrose display higher gains in dry weight and leaf development [42]. Various studies have supported the beneficial effects of these hormones in inducing a callus in Hevea and other plant species [43][44][45][46]. The optimal regeneration potential was obtained in MH media supplemented with 1 mg/L 6-BA, 3 mg/L KT, 0.06 mg/L 2, 4-D, and 0.5 mg/L GA3.…”
Section: Discussionmentioning
confidence: 99%